2021
DOI: 10.3390/en14206678
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits from Renewable Electricity Sources: A Review

Abstract: Energy generation has had several negative health impacts over the last few decades, mainly due to air pollution. One of the ways to decrease such impacts is to increase energy generation through renewable energy sources (RESs). These sources have important health co-benefits that need to be taken into consideration. This topic has been included in the literature, but research is scattered. The goal of this article is to show the status of the literature on this topic. We performed a systematic literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
2
0
1
Order By: Relevance
“…In contrast, renewable energy sources produce minimal air pollutants during operation, thereby improving air quality and public health outcomes . Studies have consistently demonstrated the health co-benefits of transitioning to renewable energy (Silva et al, 2021;Şenyapar, 2023). A comprehensive analysis by the World Health Organization (WHO) found that switching from fossil fuels to renewable energy could prevent millions of premature deaths annually by reducing air pollution-related illnesses .…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In contrast, renewable energy sources produce minimal air pollutants during operation, thereby improving air quality and public health outcomes . Studies have consistently demonstrated the health co-benefits of transitioning to renewable energy (Silva et al, 2021;Şenyapar, 2023). A comprehensive analysis by the World Health Organization (WHO) found that switching from fossil fuels to renewable energy could prevent millions of premature deaths annually by reducing air pollution-related illnesses .…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Ao contrário dos combustíveis fósseis, a energia renovável tem o potencial de contribuir para a melhoria do bem-estar humano e ambiental simultaneamente (WHO, 2021). A poluição do ar urbano e o carbono negro (fuligem) estão associados a doenças cardiovasculares e respiratórias, e a exposição a níveis nocivos de poluentes resultantes da produção e uso de combustíveis fósseis tem sido associada a mortes prematuras e perdas de produtividade (Silva et al 2021). O material particulado e o ozônio ao nível do solo também foram responsáveis por cerca de 7,4 milhões de toneladas em perdas de rendimento de soja, milho, trigo e arroz (Jorquera et al 2019).…”
Section: Energia Renovável Em Pesquisa Interdisciplinarunclassified
“…In the context of the climate crisis and sustainable development, RES non-emission of harmful substances, their lack of impact on the earth's energy balance, and their wide availability are most often emphasized [14,[92][93][94]. Moreover, the health benefits, energy security and economics of power consumption are often researched and stressed [14,95,96]. On the other hand, the drawbacks of solar energy are, for example, the high cost of installation, seasonality, and problems with storing [14].…”
Section: Threats and Opportunities For The Implementation Of Local Spatial Plan Regulations On Resmentioning
confidence: 99%